2016
DOI: 10.1890/15-1222.1
|View full text |Cite
|
Sign up to set email alerts
|

Greater carbon allocation to mycorrhizal fungi reduces tree nitrogen uptake in a boreal forest

Abstract: The central role that ectomycorrhizal (EM) symbioses play in the structure and function of boreal forests pivots around the common assumption that carbon (C) and nitrogen (N) are exchanged at rates favorable for plant growth. However, this may not always be the case. It has been hypothesized that the benefits mycorrhizal fungi convey to their host plants strongly depends upon the availability of C and N, both of which are rapidly changing as a result of intensified human land use and climate change. Using larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 53 publications
6
37
1
Order By: Relevance
“…Our results of the negative effects of N fertilization on fungi, especially arbuscular mycorrhizal fungi, and fungi to bacteria ratios in subtropical forests were in consistent with previous laboratory experiments and studies conducted in boreal, temperate and tropical forests (Högberg et al, 2003;DeForest et al, 2004;Allison et al, 2009;Van Diepen et al, 2011;Wu et al, 2013). Generally, the reduction of fungi resulted from less nutrients allocated to root and arbuscular mycorrhizal fungi due to the enhanced nutrient availability and plant nutrient acquisition by N deposition (Johnson et al, 2003;Treseder 2008;Hasselquist et al, 2016). Although we did not find significant effect of N fertilization on soil C, N and P content, our results highlighted an important direction that changes of fungal taxonomic groups in humid subtropical forests should be considered as well as the shift of the overall microbial community structure.…”
Section: Discussionsupporting
confidence: 91%
“…Our results of the negative effects of N fertilization on fungi, especially arbuscular mycorrhizal fungi, and fungi to bacteria ratios in subtropical forests were in consistent with previous laboratory experiments and studies conducted in boreal, temperate and tropical forests (Högberg et al, 2003;DeForest et al, 2004;Allison et al, 2009;Van Diepen et al, 2011;Wu et al, 2013). Generally, the reduction of fungi resulted from less nutrients allocated to root and arbuscular mycorrhizal fungi due to the enhanced nutrient availability and plant nutrient acquisition by N deposition (Johnson et al, 2003;Treseder 2008;Hasselquist et al, 2016). Although we did not find significant effect of N fertilization on soil C, N and P content, our results highlighted an important direction that changes of fungal taxonomic groups in humid subtropical forests should be considered as well as the shift of the overall microbial community structure.…”
Section: Discussionsupporting
confidence: 91%
“…However, increased exogenous C availability to P. albus did result in both a decrease in the amount of N transferred to the plant and a trend to fewer mycorrhizal root tips formed. In experiments using plant shading to alter C transfer to ECM fungi, Hasselquist et al (2016) found a similar result with less N delivery to plant tissues when C transfer was high (unshaded). The decrease in N transfer in our experiment was not likely to be associated with a scarcity of N resources for P. albus as colonies with access to high C acquired more N from the substrate and maintained a similar C : N ratio to those colonies with limited access to C. Overall, these results correspond well with previous field-based studies showing that under low-N conditions, although trees allocate more C to their roots (H€ ogberg et al, 2010;Corrêa et al, 2011), this does not appear to correspond to an increase in N gain from the fungus (Corrêa et al, 2011;N€ asholm et al, 2013;Valtanen et al, 2014).…”
Section: Researchmentioning
confidence: 78%
“…Shading experiments can reduce C allocation to belowground less destructively, allowing evaluation of the effect of reduced carbohydrate source on belowground processes. In combination with enhanced N supply, such experiments can also alter carbohydrate sinks both aboveground and belowground, allowing further definition of processes (Hasselquist et al, 2016). However, the approach has only been employed over short vegetation: crops/grasses (Manderscheid, Pacholski, & Weigel, 2010), seedlings (Mao et al, 2016), or young trees (Hasselquist et al, 2016;Walcroft, Whitehead, Kelliher, Arneth, & Silvester, 2002).…”
Section: Introductionmentioning
confidence: 99%